2022
DOI: 10.3390/tropicalmed7080144
|View full text |Cite
|
Sign up to set email alerts
|

Extended Spectrum β-Lactamase Producing Lactose Fermenting Bacteria Colonizing Children with Human Immunodeficiency Virus, Sickle Cell Disease and Diabetes Mellitus in Mwanza City, Tanzania: A Cross-Sectional Study

Abstract: Rectal carriage of extended spectrum β-lactamase-lactose fermenters (ESBL-LF) is the major risk factor for the development of subsequent endogenous infections. This study determined the patterns and factors associated with the rectal carriage of ESBL-LF among children with Human Immunodeficiency Virus (HIV), Diabetes Mellitus (DM), and Sickle Cell Disease (SCD) attending clinics at different health care facilities in the city of Mwanza, Tanzania. A cross-sectional study was conducted among children living with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 34 publications
1
3
0
Order By: Relevance
“…In the Swiss HIV cohort (2015-2016), the prevalence of 3GC-R-Ent carriers was found to be 6.7% [117], which is consistent with the rate found in healthy people (7.1%) during the same period [91]. In contrast, in low-income countries, subjects not receiving ART showed higher MDR-Ent colonization rates (e.g., 23-33% in Tanzania) than the general population [118,119]. Interestingly, in a recent analysis, carriage of ESBL-Ent was more frequent in men who have sex with men undergoing preexposure prophylaxis or living with HIV-positives and with high number of sexual partners [120].…”
Section: Community Settingsupporting
confidence: 73%
“…In the Swiss HIV cohort (2015-2016), the prevalence of 3GC-R-Ent carriers was found to be 6.7% [117], which is consistent with the rate found in healthy people (7.1%) during the same period [91]. In contrast, in low-income countries, subjects not receiving ART showed higher MDR-Ent colonization rates (e.g., 23-33% in Tanzania) than the general population [118,119]. Interestingly, in a recent analysis, carriage of ESBL-Ent was more frequent in men who have sex with men undergoing preexposure prophylaxis or living with HIV-positives and with high number of sexual partners [120].…”
Section: Community Settingsupporting
confidence: 73%
“… 16 Our findings are, however, higher than a study by Said et al, which was conducted in 2021 in Mwanza, Tanzania, which reported that about 65.9% of GNB colonising children, of whom the majority were not hospitalised, harboured ESBL genes at the same setting. 17 Therefore, the difference in study populations between the studies may explain the difference observed. Similar to previous studies published in 2020 and 2021 in Mwanza and in 2021 in Morogoro, Tanzania, 16 , 17 , 18 the majority of ceftriaxone-resistant GNB were harbouring the bla CTX-M gene.…”
Section: Discussionmentioning
confidence: 99%
“… 17 Therefore, the difference in study populations between the studies may explain the difference observed. Similar to previous studies published in 2020 and 2021 in Mwanza and in 2021 in Morogoro, Tanzania, 16 , 17 , 18 the majority of ceftriaxone-resistant GNB were harbouring the bla CTX-M gene. The predominance of bla CTX-M may be a result of successful dissemination by conjugative epidemic plasmids, which facilitates its horizontal and vertical transmission.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation